Enhancing equipment qualification testing facility for nuclear power plants: Achieving rapid temperature and pressure increase during design basis events - Ryu, Kyungha; Cho, Seonggyu; Roh, Taeho; Kim, Sangkyo; Park, Taekook; Lee, Taehyun; Park, Jongwon; Cho, Jaehyun (Nuclear engineering and technology, 2025)
The present study focuses on the development of an equipment qualification (EQ) testing facility for Class 1E equipment in nuclear power plants (NPPs), emphasizing the need to ensure safety functions under design basis events (DBEs). The Republic of Korea (ROK) has implemented international safety standards to support large NPP projects, necessitating the development of domestic EQ testing facilities to reduce the dependence on foreign facilities. To address this need, herein, a specialized facility capable of simulating harsh DBE conditions that may occur in NPPs in ROK was constructed. Through exhaustive research, target temperature and pressure profiles were developed for pressurized water reactors, and a superheated steam injection technique was devised for rapid temperature and pressure changes. The present study contributes to the advancement of domestic EQ testing capabilities, achieving up to 230 °C and 700 kPa within 30 s.